Productivity Of Construction Projects With Industrialized Building System (IBS) Technology Adoption - Akashah, Muhammad Amirul (Universiti Sains Malaysia, 2017)
Generally, the adoption of Industrialized Building System (IBS) in the construction industry throughout the world has the positive impact in improving the overall industry performance. IBS is an innovating technology that involves a reduction of site labor, lower wastage, less site materials, cleaner environment, better quality, neater and safer construction sites, faster project completion as well as cost efficient in total construction. These can contribute towards the country’s productivity in terms of the construction industry. Therefore, this research aims to discover the most relevant factor that contributes towards the productivity of construction projects with the adoption of IBS technology based on six major factors. These factors are related to the construction stages which involve design, planning, feasibility, construction and operation. A questionnaire survey method was used in this research, by distributing the questionnaire forms to contractors, consultants, developers or government agency by approaching them through the company office, site construction and online mailing. The productivity factors were ranked through the perceptions of the respondents using a quantitative analysis. From this research, the conceptual framework was developed and produced which integrates the overall results of the study. The result brings several recommendations in order to improve the productivity of IBS technology adoption.